Metasomatism and Melting of Cordilleran Lithosphere Resulting From Sediment Relamination During Shallow Subduction - C. D. Hiett; D. L. Newell; J. W. Shervais (Geochemistry, Geophysics, Geosystems, 2025)
Abstract Mantle xenoliths recovered from the modern backarc region of the northern Altiplano Plateau record metasomatism by slab‐derived silicic melts, and a suite of Quaternary volcanics suggest that melting of accreted crustal material has persisted since shallow subduction in the Oligocene. Xenoliths recovered from a suite of high‐K andesitic lava flows include phlogopite‐ and calcite‐rich orthopyroxenites and harzburgites, a wehrlite, and a phlogopite schist. Xenolith hosted calcite yields δ13C and δ18O values of −2.49 to +0.77‰ VPDB and +15.8 to +16.4‰ VSMOW, respectively, reflecting inputs of subducted marine carbonates in the metasomatizing melt. Arc‐like trace element patterns and 87Sr/86Sr ratios further support a subduction influence. Major and trace element characteristics of Quaternary potassic basalts and intermediate alkaline lavas, with the presence of mantle xenoliths, contradict magmatic differentiation or mixing models to yield intermediate composition melts. Instead, we suggest that intermediate composition lavas are derived from the melting of sediments accreted to the base of the continental lithosphere during shallow subduction in the late Eocene‐Oligocene. Melting of accreted material produces silicic alkaline melts, which react with peridotite to produce alkaline basaltic melts and residual phlogopite‐orthopyroxenites. These processes explain the observed xenolith suite and local high‐K basaltic volcanism, and the intermediate lavas may represent sediment melts that ascended to the surface minimally altered by exploiting the Cusco‐Vilconata fault system. These observations inform mass transfers during shallow subduction and melting and metasomatism in the lithospheric mantle, with implications for the generation of alkaline magmatism and rheologic weakening in cordilleran regions globally.